Low Concentration of Vitamin [D, E] and Total Antioxidant Status [TAS] in Blood Serum in Acute Kidney Injury Patients - Anwar S. Majeed; Layla A. Mustafa (African Journal of Advanced Pure and Applied Sciences, 2023)
Acute Kidney injury is usually diagnosed by measuring several biochemical variables, A decrease in vitamin (D, E) and total antioxidant status (TAS) is often associated with occurs as a result of an imbalance between oxidants and antioxidants, Vitamin (D, E) and (TAS) represent Powerful antioxidants for predicting acute kidney injury. Here, our Study aimed to estimate Vitamin (D, E) and (TAS) in acute kidney injury patients compared to the control group, and try to prove their Low Concentrations as indications of acute kidney injury